Cancer cell‐specific protein delivery by optoporation with laser‐irradiated gold nanorods. Issue 7 (5th May 2020) - Yao, Cuiping; Rudnitzki, Florian; He, Yida; Zhang, Zhenxi; Hüttmann, Gereon; Rahmanzadeh, Ramtin
ABSTRACT: The delivery of macromolecules into living cells is challenging since in most cases molecules are endocytosed and remain in the endo‐lysosomal pathway where they are degraded before reaching their target. Here, a method is presented to selectively improve cell membrane permeability by nanosecond laser irradiation of gold nanorods (GNRs) with visible or near‐infrared irradiation in order to deliver proteins across the plasma membrane, avoiding the endo lysosomal pathway. GNRs were labeled with the anti‐EGFR (epidermal growth factor receptor) antibody Erbitux to target human ovarian carcinoma cells OVCAR‐3. Irradiation with nanosecond laser pulses at wavelengths of 532 nm or 730 nm is used for transient permeabilization of the cell membranes. As a result of the irradiation, the uptake of an anti‐Ki‐67 antibody was observed in about 50 % of the cells. The results of fluorescence lifetime imaging show that the GNR detached from the membrane after irradiation. Abstract : Here, anti‐EGFR antibody Erbitux functionalized gold nanorods are specifically attached to human ovarian carcinoma cells OVCAR‐3 and irradiated with nanosecond laser pulses at wavelengths of 532 nm or 730 nm to realize membrane permeability. Antibodies can be delivered into cells, avoiding the endo lysosomal pathway. The delivered antibodies in the cells as well as the gold nanorods distribution before and after irradiation are shown with fluorescence lifetime imaging microscopy.